Response inhibition partly mediates the relationship between emotional states and creative divergent thinking - Khalil, Radwa; Lin, Lin; Karim, Ahmed A.; Godde, Ben (Creativity Research Journal, 2023)
Why can some people generate outstanding creative ideas despite receiving frustrating feedback? Although previous studies highlighted the effects of emotional states on creativity, the interactions between specific psychophysiological emotional parameters or affective states and response inhibition (RI) on creativity remain elusive. Therefore, with this study, we aimed to investigate whether RI mediates the effects of emotional states on creative thinking, specifically divergent thinking (DT), while participants receive frustrating or encouraging feedback. We induced positive and negative affect and psychophysiological arousal (PA) by manipulating feedback on performing a go/no-go task (GNGT), one of the standardized tasks for measuring RI. In other words, we provided participants with artificial feedback on GNGT to induce either frustration following (a negative emotional state) or a feeling of success (a positive emotional state). After receiving the manipulated feedback, participants performed the alternative uses task (AUT), a classical test for measuring DT. Subjective affective states were assessed using the Positive and Negative Affect Scale-Expanded Form (PANAS-X). During AUT, PA was measured through skin conductance (SC) and heart rate variability (HRV). Our data revealed that RI mediates the effect of negative affect and fatigue and enhanced PA (measured through HRV) on DT. Moreover, positive affect and PA (measured through SC) directly enhanced the three indices of DT (fluency, originality, and flexibility). Concerning the measurement of HRV, the application of time-domain HRV analyses was superior to that of frequency-domain HRV analyses. Notably, gender had strong direct and indirect effects on fluency and flexibility but not originality. In conclusion, our results suggest distinct mechanisms for modulatory effects of specific emotional states and associated psychophysiological on divergent creative thinkin
Keywords: Emotional states; Creative divergent thinking; Response inhibition; Heart rate variability; Skin conductance; Arousal